The Utilization of Aleorites Moluccana Active Charcoal as Absorbent of Lead Metal in Used Oil - Wayan N. Sugiani; Vanny M. A. Tiwow; Minarni R. Jura (Jurnal Akademika Kimia, 2021)
Candlenut (Aleurites moluccana) shell is a waste produced from the processing of the plants having a fairly hard texture. This study aimed to determine the optimum weight and contact time for the candlenut activated carbon which can absorb lead metal in used oil. Analysis of lead levels was carried out using atomic absorption spectropometry (AAS). Determination of the optimum weight and contact time of activated charcoal was carried out on various weight of 3 g, 6 g, and 9 g, as well as various times of 1, 2, and 3 hours, respectively. The results show that the optimum weight and contact time of activated charcoal are 9 g for 3 h with the percentage of lead concentration absorbed of 90.716%.